Poklicni stres in profesionalni razvoj učiteljev razrednega pouka - Modrej, Mateja; Cugmas, Zlatka (Revija za elementarno izobraževanje, 2015)
Occupational Stress and Professional Development of Primary School Teachers. The occupation of primary school teachers is considered one of the most stressful professions. The survey was used to determine the incidence of stress in 110 primary school teachers in urban and rural schools in Slovenia, depending on seniority. Its aim was to learn about stress symptoms, stressful situations and strategies to manage stress among teachers. The results show that teachers evaluate their work as a very responsible one and in majority do not think about changing their job. Teachers most often perceive physical and emotional symptoms of stress. They are faced with stressful situations when working with pupils, at their professional work, and in relations with colleagues, school management, and parents. When difficulties arise in their work, teachers most often turn for help to a colleague or the school management; and they manage their stress by going for a walk and talking to their friends.
Keywords: primary school teacher; occupational stress; urban-rural schools; seniority; stress; management